Acute Recurrent Pancreatitis in Children: A Study From the Pediatric Health Information System. Issue 3 (March 2016) - Pant, Chaitanya; Sferra, Thomas J.; Lee, Brian R.; Cocjin, Jose T.; Olyaee, Mojtaba
Abstract : ABSTRACT: We investigated acute recurrent pancreatitis (ARP) in children using a national health care database. From 2002 to 2014, 26, 435 children had a diagnosis of acute pancreatitis (AP); 10, 648 discharges were index hospitalizations. A total of 6159 children had a single hospitalization for AP, whereas 4489 (42%) children underwent 15, 787 rehospitalizations. Children experienced a median of 2 ARP-related hospitalizations with a median time between admissions of 86 days. Younger patients with a more severe index episode of AP were at a higher risk of ARP. ARP-related hospitalizations had an increased requirement for intensive care unit care compared with an index episode of AP.